2004
DOI: 10.1203/01.pdr.0000120683.68630.fb
|View full text |Cite
|
Sign up to set email alerts
|

MMP-2 and MMP-9 and Their Tissue Inhibitors in the Plasma of Preterm and Term Neonates

Abstract: Matrix metalloproteinases (MMP) and their tissue inhibitors (TIMP) are involved in a variety of physiologic growth and development and pathophysiologic inflammatory conditions. We hypothesized that 1) MMP-2 and -9 plasma activities and TIMP-1 and -2 plasma concentrations in preterm and term neonates were dependent on the gestational and postnatal age; and 2) the respective MMP and their inhibitors were deranged in the development of bronchopulmonary dysplasia (BPD) and intraventricular hemorrhage (IVH) in pret… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 22 publications
3
32
0
2
Order By: Relevance
“…Importantly, MMP-9 activity has recently been implicated in the aetiology of injuries to the immature brain. Schulz et al [7] have demonstrated that plasma levels of MMP-9 were significantly higher in infants with intraventricular haemorrhage suggesting a possible role of peripheral MMP-9 in neonatal brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, MMP-9 activity has recently been implicated in the aetiology of injuries to the immature brain. Schulz et al [7] have demonstrated that plasma levels of MMP-9 were significantly higher in infants with intraventricular haemorrhage suggesting a possible role of peripheral MMP-9 in neonatal brain injury.…”
Section: Introductionmentioning
confidence: 99%
“…They have also been observed in inflammatory pathologies of the child, as in chronic suppurative otitis media and in chronic lung diseases (Ekekezie et al, 2004;Jang et al, 2006). Both gelatinases have ben found in a variety of body fluids, namely, caphaloraquid fluid, tracheal secretion, middle ear secretion, gingival fluid, blood plasma and saliva (Ekekezie et al, 2004;Jang et al, 2006;Kettlun et al, 2003;Schulz et al, 2004;Valenzuela, 2000;Wu et al, 1997). Patients subjected to therapeutical irradiation of the maxillofacial territory have active and inactive forms of MMP-2 and MMP-9 in saliva and irradiation would increase the MMP-9 activity (Vuotila et al, 2002).…”
Section: Occurrence Of Molecules Associated With Extracellular Matrixmentioning
confidence: 99%
“…MMP ve TIMP düzeylerinin preterm bebeklerde intraventriküler hemoraji ve bronkopulmoner displazi gelişimi ile ilişkili olduğunu ve MMP-2 ve MMP-9 düzeylerinin gestasyonel yaştan etkilendiğini bildirmiş-lerdir. 4 Ekekezie ve ark. kronik akciğer hastalığı olma riski olan hastalarda ilk hafta içerisinde TIMP-1 seviyesinin düşük, MMP-9/TIMP-1 oranının, TIMP-2 ve MMP-2 seviyelerinin düşük olduğunu bildirmişlerdir.…”
Section: Bulgularunclassified
“…Entübasyon yada surfaktan ihtiyacı göstermeyen hafif ya da orta düzey RDS'li hastalar ayrıca incelenmemiştir. koryoamnionit ve intraventriküler kanama gibi patolojilerde MMP ve TIMP düzeylerinin değişiklik göstermesi, olayın sadece akciğer ile sınırlı olmadığını ve sistemik etkilerinin de olabileceğini göstermektedir 3,4 . Tüm bu nedenlerle serumda MMP ve TIMP düzeyinin belirlenmesinin akciğer hasarının göstergesi olabileceği düşünülmüştür.…”
Section: Introductionunclassified